2018
DOI: 10.3389/fphar.2018.00176
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Fission Is Required for Angiotensin II-Induced Cardiomyocyte Apoptosis Mediated by a Sirt1-p53 Signaling Pathway

Abstract: Hypertension-induced cardiac apoptosis is a major contributor to early-stage heart-failure. Our previous studies have found that p53-mediated mitochondrial fission is involved in aldosterone-induced podocyte apoptosis. However, it is not clear that whether p53-induced mitochondrial fission is critical for hypertensive Angiotensin II (AngII)-induced cardiomyocyte apoptosis. In this study, we found that inhibition of the mitochondrial fission protein Drp1 (dynamin-related protein 1) by Mdivi-1 prevented cardiomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 33 publications
(42 reference statements)
2
35
0
Order By: Relevance
“…Increasing evidence indicates that mitochondrial fission promotes the initiation of mitochondrial apoptosis . Our transmission electron microscopy assay revealed that mitochondria presented as elongated filamentous structures in control cells, but exhibited small and punctate mitochondria in IR‐783‐treated cells (Figure A).…”
Section: Resultsmentioning
confidence: 78%
“…Increasing evidence indicates that mitochondrial fission promotes the initiation of mitochondrial apoptosis . Our transmission electron microscopy assay revealed that mitochondria presented as elongated filamentous structures in control cells, but exhibited small and punctate mitochondria in IR‐783‐treated cells (Figure A).…”
Section: Resultsmentioning
confidence: 78%
“…Previous studies have demonstrated that SIRT1 deacetylates its downstream targets, including NF-κB, Foxos, p53, and peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α), to regulate apoptosis, inflammation, and oxidative stress and protect organs from IR injury [65]. Additionally, recent studies have shown that the SIRT1/PGC-1α [66] and SIRT1/p53 [67] pathways inhibited Drp1-mediated mitochondrial fission and subsequently induced mitochondrial dysfunction and mitochondriaderived ROS production, resulting in the attenuation of cell apoptosis and death. Consistent with previous studies, our results showed that RNLS administration significantly increased the activity of SIRT1 and protected against oxidative stress injury induced by t-BHP.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in mitochondrial morphology also contribute to apoptotic responses in the heart. For example, angiotensin II‐induced hypertensive hearts demonstrate a downregulation of SIRT1, thus allowing p53 acetylation and Drp1‐dependent mitochondrial fission, from which mitochondrial fragmentation eventually results in cardiomyocyte apoptosis (Qi et al ., ). Additionally, a down‐regulation of cardiac dual‐specificity protein phosphatase 1 in acute I/R injury activates mitochondrial fission and cardiomyocyte apoptosis (Jin et al ., ).…”
Section: Mechanisms Of Mitochondria‐mediated Cell Death In Cardiac DImentioning
confidence: 97%